Long COVID syndrome‐associated brain fog. Issue 3 (24th October 2021) - Asadi‐Pooya, Ali A.; Akbari, Ali; Emami, Amir; Lotfi, Mehrzad; Rostamihosseinkhani, Mahtab; Nemati, Hamid; Barzegar, Zohreh; Kabiri, Maryam; Zeraatpisheh, Zahra; Farjoud‐Kouhanjani, Mohsen; Jafari, Anahita; Sasannia, Fateme; et al.
Abstract: We investigated the frequency of brain fog in a large cohort of patients with documented coronavirus disease‐2019 (COVID‐19) who have survived the illness. We also scrutinized the potential risk factors associated with the development of brain fog. Adult patients (18–55 years of age), who were referred to the healthcare facilities anywhere in Fars province from February 19, 2020 to November 20, 2020 were included. All patients had a confirmed COVID‐19 diagnosis. In a phone call, at least 3 months after their discharge from the hospital, we obtained their current information. A questionnaire was specifically designed for data collection. In total, 2696 patients had the inclusion criteria; 1680 (62.3%) people reported long COVID syndrome (LCS). LCS‐associated brain fog was reported by 194 (7.2%) patients. Female sex (odds ratio [OR]: 1.4), respiratory problems at the onset (OR: 1.9), and intensive care unit (ICU) admission (OR: 1.7) were significantly associated with reporting chronic post‐COVID "brain fog" by the patients. In this large population‐based study, we report that chronic post‐COVID "brain fog" has significant associations with sex (female), respiratory symptoms at the onset, and the severity of the illness (ICU admission).